Targeted molecular investigation in patients within the clinical spectrum of Auriculocondylar syndrome. Issue 4 (22nd March 2017) - Romanelli Tavares, Vanessa L.; Zechi‐Ceide, Roseli M.; Bertola, Debora R.; Gordon, Christopher T.; Ferreira, Simone G.; Hsia, Gabriella S. P.; Yamamoto, Guilherme L.; Ezquina, Suzana A. M.; Kokitsu‐Nakata, Nancy M.; Vendramini‐Pittoli, Siulan; Freitas, Renato S.; Souza, Josiane; et al.
Abstract : Auriculocondylar syndrome, mainly characterized by micrognathia, small mandibular condyle, and question mark ears, is a rare disease segregating in an autosomal dominant pattern in the majority of the families reported in the literature. So far, pathogenic variants in PLCB4, GNAI3, and EDN1 have been associated with this syndrome. It is caused by a developmental abnormality of the first and second pharyngeal arches and it is associated with great inter‐ and intra‐familial clinical variability, with some patients not presenting the typical phenotype of the syndrome. Moreover, only a few patients of each molecular subtype of Auriculocondylar syndrome have been reported and sequenced. Therefore, the spectrum of clinical and genetic variability is still not defined. In order to address these questions, we searched for alterations in PLCB4, GNAI3, and EDN1 in patients with typical Auriculocondylar syndrome (n = 3), Pierre Robin sequence‐plus (n = 3), micrognathia with additional craniofacial malformations (n = 4), or non‐specific auricular dysplasia (n = 1), which could represent subtypes of Auriculocondylar syndrome. We found novel pathogenic variants in PLCB4 only in two of three index patients with typical Auriculocondylar syndrome. We also performed a detailed comparative analysis of the patients presented in this study with those previously published, which showed that the pattern of auricular abnormality and full cheeks were associated with molecularly characterized individuals with Auriculocondylar syndrome. Finally, our data contribute to a better definition of a set of parameters for clinical classification that may be used as a guidance for geneticists ordering molecular testing for Auriculocondylar syndrome. © 2017 Wiley Periodicals, Inc.